New norfloxacin/nitric oxide donor hybrids: Synthesis and nitric oxide release measurement using a modified Griess colorimetric method - Aziz, Hossameldin Ali; Moustafa, Gamal Abdeltawab Idris; Abbas, Samar Hafez; Derayea, Sayed Mohamed; Abuo-Rahma, Gamal El-Din Ali Ahmed (European Journal of Chemistry, 2017)
Oximes and nitrate esters are considered as important nitric oxide (NO) donors with diverse biological activities. Herein, we report the synthesis and characterization of new oxime and nitrate ester derivatives of norfloxacin as potential NO donor hybrids with expected synergistic antimicrobial activity. The release of NO from those hybrids was measured by a modified Griess method in which p-nitroaniline was employed instead of sulfanilamide. The increased electrophilicity of the intermediate 4-nitroaniline diazonium salt accelerated the coupling process and shortened the overall assessment time. The improved detection limits and enhanced sensitivity would pave the way for the future application of this method in nitrite determination in biological or non-biological systems.